Identity and first record of the spittlebug Mahanarva bipars (Hemiptera: Auchenorrhyncha: Cercopidae) of sugarcane in Colombia - Peck, DC; Rodríguez Chalarca, Jairo; Gómez, L.A. (Florida Entomological Society, 2004)
Mahanarva bipars (Walker) is identified as the species causing the first spittlebug outbreak in Colombian sugarcane. Information on the biology, host plants and geographic range are absent from the literature. Therefore, we summarize field observations on infestation levels and location of feeding sites, laboratory observations on size and adult color pattern variation, and known locality information that indicates distribution is restricted to western Colombia.